Dual Ice Crystal Imager (D-ICI): images of snow particles from Kiruna on 2014-10-19 with size, area, and fall speed measurements ... : Dual Ice Crystal Imager (D-ICI): bilder av snöpartiklar från Kiruna den 2014-10-19 med storlek, yta, och fallhastighetsmätningar ... - Kuhn, Thomas (Luleå University of Technology, 2019)
Accurate predictions of snowfall require good knowledge of the microphysical properties of the snow ice crystals and particles. Shape is an important parameter as it influences strongly the scattering properties of the ice particles, and thus their response to remote sensing techniques such as radar measurements. The fall speed of ice particles is another important parameter for both numerical forecast models as well as representation of ice clouds and snow in climate models, as it is responsible for the rate of removal of ice from these models. A new ground-based in-situ instrument, the Dual Ice Crystal Imager (D-ICI), has been developed to determine snow ice crystal properties and fall speed simultaneously. The instrument takes two high-resolution pictures of the same falling ice particle from two different viewing directions. Both cameras use a microscope-like set-up resulting in an image pixel resolution of approximately 4μm/pixel. One viewing direction is horizontal and is used to determine fall speed ... : Ett nytt instrument, kallad Dual Ice Crystal Imager (D-ICI), har utvecklats för att mäta samtidigt mikrofysikaliska egenskaper och fallhastighet av snöpartiklar. Instrumentet tar bilder av partiklar från två olika riktningar med en upplösning av 4μm/pixel. Första mätningar med D-ICI i Kiruna, norra Sverige (67.8N, 20.4E), den 2014-10-19 presenteras. Både bilder och egenskaper framtagna av dessa ingår i datasetet. Datasetet ligger till grund för artikeln Kuhn, T. and Vázquez-Martín, S.: Microphysical properties and fall speed measurements of snow ice crystals using the Dual Ice Crystal Imager (D-ICI), Atmos. Meas. Tech., 13, 1273–1285, https://doi.org/10.5194/amt-13-1273-2020, 2020. För mer information se den engelska katalogsidan: https://snd.gu.se/en/catalogue/study/SND1129 Data består av bilder från två kameror, top view och side view. Bilderna finns i mappar "20141018_180609_top" (top view) och "20141018_180728_side" (side view). Mappen av top-view bilder innehåller också resultat från bildanalys för att ...